Power Consumption Analysis of a BLDC 24V 250W Electric Bike on An Assembled Lithium-ion Battery Pack - Wahyudi Fachrul Syafra; Purwantono Purwantono; Hasanuddin Hasanuddin; Arwizet K (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2020)
This research is using experimental method. Tests carried out on electric bicycles with 250 Watt Brushless DC motor drive. The total power consumption is obtained through testing the use of electric bicycles which starts from the maximum battery condition until the bike cannot move. The battery used is a type of lithium ion assembly with a total capacity of 29.12 Volt 20Ah. In testing, the bike was driven at maximum speed, with a 65kg rider. In the first test, a distance of 30.6 Km was reached with a power consumption of 1041.1 Watt, 112 minutes of travel time. The second test as far as 31.1 Km requires 1090.8 Watts of power takes 117 minutes. And the 3rd test reached a distance of 35.9 Km with 1178 Watts of power and 128 minutes of travel time. It was also found that the battery was unable to move the bike at the lowest voltage of 22.1 Volt. Penelitian ini menggunakan metode eksperimen. Pengujian dilakukan pada sepeda listrik dengan penggerak motor Brushless DC 24V 250 Watt. Total konsumsi daya didapat melalui pengujian pemakaian sepeda listrik yang dimulai dari kondisi baterai maksimum sampai sepeda tidak dapat bergerak. Baterai yang digunakan adalah jenis lithium ion rakitan dengan total kapasitas 29.12 Volt 20Ah. Pada pengujian, sepeda digerakan dengan kecepatan maksimalnya, dengan baban pengendara 65Kg. Pada pengujian pertama tercapai jarak 30.6 Km dengan konsumsi daya 1041.1 Watt, waktu tempuh 112 menit. Pengujian ke-2 sejauh 31.1 Km membutuhkan daya 1090.8 Watt waktu tempuh 117 menit. Dan pengujian ke-3 mencapai jarak 35.9 Km dengan daya 1178 Watt dan waktu tempuh selama 128 menit. Didapati juga hasil bahwa baterai tidak mampu mengerakan sepeda pada tegangan terendah sebesar 22.1 Volt.